Bringing New Light to Schools: Dolf Schnebli’s Works - Pennati, Lucia (Vysoké učení technické v Brně, Fakulta architektury, 2021)
This paper deals with the pedagogical agency of space and the role light plays in learning. In the post-war context of the 1950s and 1960s, the control of light was an architectural tool that demonstrated the didactic position of the architect in designing schools. Through a critical examination of Swiss architect Dolf Schnebli’s work, his dynamical process of designing light and its representational methods, the paper captures how school design engaged with practical and theoretical ideas about light. It argues that the architect, through designing light, fulfilled one aspect of the pedagogical agency of space, in terms of creating the most appropriate setting for education.
Keywords: architecture; education; school; pedagogy; light; drawing